2023
DOI: 10.1093/ofid/ofad193
|View full text |Cite
|
Sign up to set email alerts
|

Anaplasmosis in Pennsylvania: Clinical Features, Diagnosis, and Outcomes of Patients Diagnosed With Anaplasma phagocytophilum Infection at Hershey Medical Center From 2008 to 2021

Abstract: Anaplasmosis is an emerging infection in the United States and in particular, Pennsylvania. We highlight the abrupt rise in cases of anaplasmosis in the past decade in the state of Pennsylvania with the hope of increasing clinician awareness. We identified a cohort of 61 patients diagnosed with anaplasmosis at our institution as well as cases reported to the Department of Health. From our review, we not only identified an increase in cases over time but what appears to be an expansion further into central and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Their most commonly presenting symptom was subjective fever (85%), which was a chief complaint for our patient. The study reported elevated liver enzymes and thrombocytopenia as common laboratory manifestations (71% and 69% of patients, respectively), and less often (27%) leukopenia, all three were seen in our patient [9]. Early empiric treatment is vitally important, as HGA can be deadly if untreated or if treatment is delayed.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…Their most commonly presenting symptom was subjective fever (85%), which was a chief complaint for our patient. The study reported elevated liver enzymes and thrombocytopenia as common laboratory manifestations (71% and 69% of patients, respectively), and less often (27%) leukopenia, all three were seen in our patient [9]. Early empiric treatment is vitally important, as HGA can be deadly if untreated or if treatment is delayed.…”
Section: Discussionmentioning
confidence: 45%
“…By looking at the Pennsylvania Department of Health (DOH) data, they found cases were spreading geographically, with explosions in numbers in Eastern, Central, and Western counties of Pennsylvania. Less than 10 cases were reported in 2012 to the Pennsylvania DOH, while in 2021, there were more than 600 cases reported [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation